(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
This article examines the main points of migration processes related to the international migration, and also, analyzes the causes and consequences of migration. In addition, the article studies the relationship between migration and development and its impact on the socio-economic situation in countries of origin and destination. Globalization, demographic aging in developed countries, the development of the global labor market, the formation of a stable demand for migrant labor, a huge flow of migrant remittances - all this today gives international migration, especially international migration, a whole new meaning. International migration is an integral part of the modern world order. Today, migration is an important phenomenon, related to powerful economic forces: large differences in wages and employment opportunities, and also increase in income. However, it should be taken into account that migration presents both challenges and opportunities for both receiving and sending countries. Migration currently also has a significant impact on the socio-economic progress of countries located in Central Asia. Currently, the countries of Central Asia have the potential to solve numerous social problems, replenish budgets and improve the financial situation of people through labor exports. The experience of many countries demonstrates the practical potential of labor migrants to improve the living standards of a significant part of the population and contribute to the economic development of the country. Analyzing the migration situation in Central Asian countries can help identify important patterns that are critical for formulating development-oriented migration policies. Key words: Regional interdependence, international and intraregional migration, International Organization for Migration (IOM), Kazakhstan, Kyrgyz Republic, Tajikistan, Uzbekistan, socio-economic consequences, Central Asia, economic development.